2021
DOI: 10.5114/cipp.2021.105732
|View full text |Cite
|
Sign up to set email alerts
|

Social dominance orientation predicts lower moral condemnation of causing harm to animals

Abstract: BackgroundRecent studies and theorizing (SD-HARM model) suggested that social dominance orientation (SDO) constitutes the ideological foundation of negative attitude towards animals and acceptance of their exploitation. At the same time, right-wing authoritarian-ism (RWA) is expected to predict speciesist beliefs only when they are perceived as part of societal tradition. The present studies investigated these predictions with moral condemnation of harm done to animals by humans as an indicator of speciesism.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Individual factors related to our relationship with animals could be classified into two broad categories: relatively stable dispositions or factors more susceptible to change. Relatively stable dispositions include factors negatively related to violence against animals, such as empathy [27,[36][37][38][39], moral idealism [40,41], the moral foundation of care [4,12], values such as universalism [42], as well as positively related factors: dark triad traits [43][44][45], moral relativism [40,41], the moral foundation of authority [4,12], social dominance orientation [46], and values such as tradition, obedience, and security [42,47,48].…”
Section: Instrumental Violence Against Animalsmentioning
confidence: 99%
“…Individual factors related to our relationship with animals could be classified into two broad categories: relatively stable dispositions or factors more susceptible to change. Relatively stable dispositions include factors negatively related to violence against animals, such as empathy [27,[36][37][38][39], moral idealism [40,41], the moral foundation of care [4,12], values such as universalism [42], as well as positively related factors: dark triad traits [43][44][45], moral relativism [40,41], the moral foundation of authority [4,12], social dominance orientation [46], and values such as tradition, obedience, and security [42,47,48].…”
Section: Instrumental Violence Against Animalsmentioning
confidence: 99%
“…People who score higher on SDO also score higher on speciesist attitudes (Caviola et al, 2019;Dhont et al, 2016;Graça et al, 2018;Hopwood & Bleidorn, 2020). They are more likely to think that hunting and fishing are justified (Hopwood & Bleidorn, 2020), more strongly endorse the use of animals by humans (Hyers, 2006), and are less likely to condemn acts of animal cruelty (Jarmakowski-Kostrzanowski & Radkiewicz, 2021). Several studies have shown that meat eaters score higher on SDO than vegetarians or vegans Krings et al, 2021;Veser et al, 2015) and high-SDO individuals are less motivated to reduce their meat consumption because of animal welfare concerns (Hopwood & Bleidorn, 2020).…”
Section: Prejudice Against Humans and Animalsmentioning
confidence: 99%
“…In Study 1A, we would like to show the specificity of the SI construct in relation to right-wing authoritarianism (RWA) and social dominance orientation (SDO). Numerous studies ( Asbrock et al, 2010 ; Duckitt & Sibley, 2007 ; Jarmakowski-Kostrzanowski & Radkiewicz, 2021 ; Roccato & Ricolfi, 2005 ) have shown that RWA and SDO independently predict generalized negativity to out-groups and moral condemnation of harming animals. The dual-process model of prejudice (DPM – Duckitt, 2006 ) proposes that RWA expresses the motivational goal of group security and order, whereas SDO expresses the motivational goal of group power and dominance.…”
Section: Introductionmentioning
confidence: 99%